2008
DOI: 10.1007/s10528-008-9166-6
|View full text |Cite
|
Sign up to set email alerts
|

SLC11A1 Polymorphisms Are Associated with the Risk of Chronic Obstructive Pulmonary Disease in a Korean Population

Abstract: The solute carrier family 11 member 1 (SLC11A1) protein plays important roles in macrophage activation and displays pleiotropic effects on various macrophage functions, including the regulation of tumor necrosis factor-alpha (TNF-alpha), interleukin-1beta (IL-1beta), and oxidative burst. Considering the important roles of macrophage in the pathogenesis of chronic obstructive pulmonary disease (COPD), we hypothesized that the SLC11A1 gene may act as a low-penetrance susceptibility gene for COPD. To test this hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Signaling pathways include immune system [109], signal transduction [110], extracellular matrix organization [111], adaptive immune system [112], neutrophil degranulation [113], innate immune system [114], metabolism [115], diseases of metabolism [116] and Hemostasis [117] were responsible for advancement of COPD. PTGS2 [118], IL6 [119], CSF3 [120], CXCL8 [121], CXCL1 [122], SOCS3 [123], CCL3 [124], CCL5 [125], VCAM1 [126], CXCL13 [127], CXCL5 [128], CXCL12 [129], FGG (fibrinogen gamma chain) [130], IL1B [131], AREG (amphiregulin) [132], SERPINE1 [133], OSM (oncostatin M) [134], CCL11 [135], MFAP4 [136], APLN (apelin) [137], IL1RN [138], IFNG (interferon gamma) [139], CX3CL1 [140], CDKN1A [141], ICAM1 [142], SNAI1 [143], CD34 [144], IL33 [145], FASLG (Fas ligand) [146], FGF7 [147], TNF (tumor necrosis factor) [148], GDF15 [149], CCL22 [150], IL2 [151], CXCR6 [152], KLF5 [153], MCL1 [154], SRF (serum response factor) [155], FABP4 [156], CYP2C19 [157], CXCR4 [158], FOXC1 [159], EPHX1 [160], ANXA1 [161], DUSP6 [162], CPA3 [163], MYH10 [164], ICOS (inducible T cell costimulator) [165], CD1C [166], CD96 [167], S100A9 [168], FKBP5 [169], HMOX1 [170], PRTN3 [171], MARCO (macrophage receptor with collagenous structure) [172], STAB1 [173], SIGLEC9 [174], SLC11A1 [175], BPI (bactericidal permeability increasing protein) [176], PGF (placental growth factor) [177], FASN (fatty acid synthase) [178], S100A4 […”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include immune system [109], signal transduction [110], extracellular matrix organization [111], adaptive immune system [112], neutrophil degranulation [113], innate immune system [114], metabolism [115], diseases of metabolism [116] and Hemostasis [117] were responsible for advancement of COPD. PTGS2 [118], IL6 [119], CSF3 [120], CXCL8 [121], CXCL1 [122], SOCS3 [123], CCL3 [124], CCL5 [125], VCAM1 [126], CXCL13 [127], CXCL5 [128], CXCL12 [129], FGG (fibrinogen gamma chain) [130], IL1B [131], AREG (amphiregulin) [132], SERPINE1 [133], OSM (oncostatin M) [134], CCL11 [135], MFAP4 [136], APLN (apelin) [137], IL1RN [138], IFNG (interferon gamma) [139], CX3CL1 [140], CDKN1A [141], ICAM1 [142], SNAI1 [143], CD34 [144], IL33 [145], FASLG (Fas ligand) [146], FGF7 [147], TNF (tumor necrosis factor) [148], GDF15 [149], CCL22 [150], IL2 [151], CXCR6 [152], KLF5 [153], MCL1 [154], SRF (serum response factor) [155], FABP4 [156], CYP2C19 [157], CXCR4 [158], FOXC1 [159], EPHX1 [160], ANXA1 [161], DUSP6 [162], CPA3 [163], MYH10 [164], ICOS (inducible T cell costimulator) [165], CD1C [166], CD96 [167], S100A9 [168], FKBP5 [169], HMOX1 [170], PRTN3 [171], MARCO (macrophage receptor with collagenous structure) [172], STAB1 [173], SIGLEC9 [174], SLC11A1 [175], BPI (bactericidal permeability increasing protein) [176], PGF (placental growth factor) [177], FASN (fatty acid synthase) [178], S100A4 […”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the possible function of NRAMP1 gene polymorphisms in susceptibility and clinical outcome of RA for a Spanish population was performed by Rodriguez et al [21], and found effects on RA with radiological severity by promoter polymorphisms NRAMP1 gene. Rs1059823 has been reported to be associated with tuberculosis in East India [22], type 1 diabetes of European ancestry population [23], and chronic obstructive pulmonary disease of a Korean population [24].…”
Section: Discussionmentioning
confidence: 99%